2018
DOI: 10.12659/msm.907224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Critical Genes and Five Prognostic Biomarkers Associated with Colorectal Cancer

Abstract: BackgroundColorectal cancer (CRC) is a common malignant tumor with high incidence and mortality worldwide. The aim of this study was to evaluate the association between differentially expressed genes (DEGs), which may function as biomarkers for CRC prognosis and therapies, and the clinical outcome in patients with CRC.Material/MethodsA total of 116 normal mucous tissue and 930 CRC tissue datasets were downloaded from the Gene Expression Omnibus database (GEO) and The Cancer Genome Atlas (TCGA). After screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…The eight-gene signature also pushed the limitation of traditional TNM stage for prognostic prediction due to molecular heterogeneity in CRC. Currently, several gene signatures have been reported for prognostic prediction of CRC [63][64][65][66]. Compared to the reported signatures, the uniqueness of this study was that LASSO regression analysis could execute feature selection and shrinkage and screen highly correlated genes, which determined the optimal genes to participate in subsequent signature building [66].…”
Section: Discussionmentioning
confidence: 99%
“…The eight-gene signature also pushed the limitation of traditional TNM stage for prognostic prediction due to molecular heterogeneity in CRC. Currently, several gene signatures have been reported for prognostic prediction of CRC [63][64][65][66]. Compared to the reported signatures, the uniqueness of this study was that LASSO regression analysis could execute feature selection and shrinkage and screen highly correlated genes, which determined the optimal genes to participate in subsequent signature building [66].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of these two proteins could be due to a favoring age-associated changes and premature aging in HIV-infected individuals with prolonged exposure to cART. The decreased expression of NT3 was also observed in colorectal cancer [39], while increased levels of plasma MMP1 have been associated with coronary atherosclerosis [40] and cancers 14 [41,42] further provide evidence to support the role of these proteins in disease development during aging.…”
Section: Discussionmentioning
confidence: 78%
“…With advances in RNA sequencing (RNA-seq) and microarray profiling techniques, a large number of abnormally expressed lncRNAs have been identified in various cancers [19]. Huang et al [20] identified hundreds of CRC-associated DEGs based on the GEO and TCGA database. An et al [21] found 35 genes that were significantly associated with patient survival based on the transcription profile of multistage carcinogenesis and bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%